Maternal and Cord Blood Levels of Serum Amyloid A, C-Reactive Protein, Tumor Necrosis Factor-α, Interleukin -1β, and Interleukin-8 During and After Delivery - Luciane Marzzullo Cicarelli; Adriana Guimarães Perroni; Marcelo Zugaib; Paulo Basto de Albuquerque; Ana Campa (Mediators of Inflammation)
C-reactive protein (CRP) and serum amyloid A (SAA) are acute-phase proteins mainly synthesized by the liver in response to some cytokines. They are potentially useful to diagnosing infection and monitoring different clinical conditions. The aim of this study was to measure SAA and CRP in maternal and cord blood during and after delivery and try to correlate these proteins with tumor necrosis factor-α, interleukin -1β, and interleukin-8. Acute-phase proteins and cytokines were measured by ELISA in 24 healthy pregnant women undergoing vaginal delivery or Cesarean section. Cord blood samples in addition to maternal blood were collected. SAA and CRP reached the maximum maternal serum levels 24 hours after delivery, while cytokines remained constant over time. SAA and CRP were significantly higher in maternal serum than in newborn's (P<.001) at the moment of delivery. SAA and CRP, regardless of the type of delivery, reproduce the common pattern observed in most inflammatory conditions. Proinflammatory cytokine serum levels do not mirror the increase in SAA and CRP levels.